Correlation of Quantitative Diffusion-Weighted MR Parameters and SUVmax from 18-FDG PET-CT in Lung Cancer: A Prospective Observational Study - Goyal, Jitin; Jajodia, Ankush; Koyyala, Venkata Pradeep Babu; Bansal, Abhishek; Batra, Ullas; Pasricha, Sunil; Puri, Sunil; Chaturvedi, Arvind K. (Indian Journal of Medical and Paediatric Oncology, 2023)
Background Diffusion-weighted magnetic resonance imaging (DW-MRI) sequences report the cellularity in tissues and 18-fluorodeoxyglucose (18-FDG) positron emission tomography–computed tomography (PET-CT) provides information on glucose metabolism in cells, associated to tumor aggressiveness. The aim of this study was to assess the correlation between quantitative diffusion-weighted magnetic resonance parameters and maximum standardized uptake value (SUVmax) using 18-FDG PET-CT in lung cancer and metastatic lymph nodes.Methods Histologically proven 29 patients of lung cancers were subjected to 18-FDG PET-CT and DW-MRI (parameters: repetition time/time to echo [TR/TE] = 4,000/76 ms; b-values = 0, 400, and 800 s/mm2) between June 2018 and June 2019. SUVmax was calculated on the PET-CT images representing region of interest (ROI) in the tumor. The apparent diffusion coefficient (ADC) values were quantified by placing an ROI over the tumor at a high b-value of 800 mm2/s. Statistical analyses for correlation between SUVmax and ADC were done using Pearson's correlation coefficient (r).Results Significant negative correlation was observed between analyses of ADC and SUVmax for primary lesions of all nonsmall-cell lung cancers (NSCLCs; p < 0.05) and its histological subtype adenocarcinoma (p < 0.05) but not squamous cell carcinomas (p = 0.35). Significant negative correlation was also observed for metastatic lymph nodes of adenocarcinoma (p < 0.05) but not for metastatic lymph nodes of all NSCLCs (p = 0.05) or squamous cell carcinomas (p = 0.55).Conclusions Diffusion-weighted imaging (DWI) with ADC may represent a new prognostic marker due to a significant negative correlation between ADC determined by DWI and SUVmax by PET-CT in NSCLCs. Furthermore, DWI-MRI of the thorax can be added to routine 18-FDG PET-CT for staging and response assessment in lung cancer in prospects.
Keywords: 18-FDG PET-CT; apparent diffusion coefficient (ADC); nonsmall-cell lung cancer (NSCLC); SUVmax